The influence of tensile strain on the pore size and flow capability of needle-punched nonwoven geotextiles. Issue 6 (6th May 2016) - Wu, C. S.; Hong, Y. S.
Abstract : This work studies the effect of tensile strain on the pore size and the flow capability of needle-punched nonwoven geotextiles. Laboratory tests were conducted to investigate the variations of pore size, thickness, porosity and mean discharge velocity of water through geotextile samples (permittivity) while under different uniaxial and biaxial tensile strains ranging from 0 to 20%. Comparison of test and predicted results suggests the values of the shape factor β, describing path tortuosity and the dimensionless parameter ξ to account for the evaluations of permeability and filtration opening size for needle-punched nonwoven geotextiles under various tensile strains. The experimental data collected from three needle-punched nonwoven geotextiles show that strained geotextiles exhibit smaller pore size than unstrained geotextiles. The mean discharge velocity of water through strained geotextiles tends to decrease initially, with an increase in tensile strain for geotextiles in low strain regions, but this decreasing trend of mean discharge velocity then reverses for the same geotextiles submitted to higher strain.